Serum amyloid A induces interleukin-1β secretion from keratinocytes via the NACHT, LRR and PYD domains-containing protein 3 inflammasome. (2nd January 2015) - Yu, N; Liu, S; Yi, X; Zhang, S; Ding, Y
Summary: Interleukin (IL)-1β is now emerging as a critical cytokine in the pathogenesis of T helper type 17 (Th17)-mediated skin diseases, including psoriasis. Psoriatic keratinocytes are a major source of IL-1β; however, the mechanisms triggering IL-1β processing remain unknown. Recently, an acute-phase protein serum amyloid A (SAA) has been identified as a danger signal that triggers inflammasome activation and IL-1β secretion. In this study, we detected increased SAA mRNA and protein expression in psoriatic epidermis. In cultured keratinocytes, SAA up-regulated the expression of pro-IL-1β and secretion of mature IL-1β. On the transcriptional level, blocking Toll-like receptor-2 (TLR-2), TLR-4 or nuclear factor kappa B (NF-κB) attenuated SAA-induced expression of IL-1β mRNA. SAA up-regulated caspase-1 and NACHT, LRR and PYD domains-containing protein 3 (NLRP3) expression in keratinocytes. Inhibiting caspase-1 activity and silencing NLRP3 decreased IL-1β secretion, confirming NLRP3 as the SAA-responsive inflammasome on the post-transcriptional level. The mechanism of SAA-triggered NLRP3 activation and subsequent IL-1β secretion was found to involve the generation of reactive oxygen species. Finally, the expression of SAA by keratinocytes was up-regulated by IL-17A. Taken together, our results indicate that keratinocyte-derived SAA triggers a key inflammatory mediator, IL-1β, via NLRP3 inflammasome activation, providing new potential targets for the treatment of this chronic skin disease.